معاشرہ کی اجتماعی تربیت قصص القرآن کی روشنی میں: Societal Transformation: Reflections from Qur'anic Stories - Mehmood Ali; Dr. Kaleem Ullah (Al Manhal Research Journal, 2024)
Indeed, Allah has revealed this Noble Qur'an as guidance for mankind, selecting from various styles of expression those that are most effective in influencing hearts and minds. One such style is the narration of Quranic stories about previous prophets and their communities, illustrating the principle of divine retribution based on one's actions. Many of these stories depict scenarios where a certain person committed a particular crime and was subsequently punished accordingly. However, the question arises for the reader: how can we benefit from these stories while living in a world different from theirs, facing circumstances unlike those depicted? This is the focal point of our research, as we delve into the noble purposes and objectives of storytelling in the Quran, discussing their role in societal reform and individual upbringing."